G162 'Mind the Gap' – Observable features of parent-child interactions amongst neglected children aged 0 to 13 years. (7th April 2014) - Naughton, AM; Maguire, SA; Williams, B; Mann, MK; Cowley, L; Tempest, V; Kemp, AM
Abstract : Aim: Neglect has far reaching consequences on a child's emotional, psychological and social development. Our systematic review aims to identify the evidence base for observable features of the parent child interaction amongst neglected or emotionally abused children. Methods: Using 80 key words & phrases we searched 18 databases and seven websites for the period 1950–2012, supplemented by handsearching journals and references. Of 10, 206 abstracts identified, 922 full texts were scanned, and 188 articles reviewed by two independent reviewers (from a panel of paediatricians, child & educational psychologists, psychiatrists, teachers and social workers), using standardised critical appraisal methods. Included: age < 13 years, observed features in the parent-child interaction (both in the parent and/or the child during the interaction), neglect or emotional abuse confirmed by explicit criteria. Excluded: longterm outcome data, mixed forms of maltreatment where neglect could not be separated. Results: 18 studies met the inclusion criteria and reported direct observation of the parent child interaction, 16 case control, 2 longitudinal cohort studies. Distinguishing features observed in the parent-child interaction included: hostility from parent (8 studies), showing less verbal interactions, more punishment, criticism & verbal aggression, less positive verbalisation. Unavailability and lack of attunement (12 studies): parents less responsive, less support to children completing tasks, interaction developmentally inappropriate, more likely to end/less likely to initiate interaction, less eye contact, less emotional discussion. Neglected children display more negativity in the parent-child interaction (2 studies) showing less verbal and non verbal affection and more physical aggression towards parents. Parental risk factors such as poor social competence, substance abuse, mental health problems of mothers and domestic violence in families were also confirmed. Conclusions: Most paediatric consults offer the opportunity to observe the parent-child interaction, thus all practitioners could identify worrying features which merit further evaluation. The parent who is developmentally inappropriate with their child; a child displaying physical aggression towards their parent or concerning parent–child interaction requires recording and consideration of safeguarding implications.